Estudio de la influencia de las practicas alimentarias en los niveles de glicemia de los pacientes con diabetes mellitus tipoII, que asisten al Hospital Jaime RoldOs Aguilera de la ciudad de ventanas, durante el periodo comprendido entre 1 junio - 31 diciembre 2011 - Cercado Arrieta, Nelly Xiomara (2011)
The present work has as objective to determine how the alimentary practices alter the glicemia levels in patient with diabetes mellitus type II. Material and Methods: One carries out an investigation type cuali - quantitative, qualitative to understand the causes and implicit circumstances in the problem of quantitative type, to be able to measure indicators and variables of the investigation. In the 2011 100 patients were assisted by pathologies considered as diabetes mellitus type II in the hospital Jaime Roldos Aerie by which the sample of alone study 40 patients that fulfilled the inclusion approaches was chosen. The evaluated variables were the patient's age with diabetes mellitus type II, sex; you practice alimentary, glicemia levels in blood and socioeconomic aspects. Results: The age of 65 to 74 years that it is the age group that is more affected a bigger illness incidence exists in the group of women; people with diabetes not maintain a type of patterns or an alimentary régime appropriate. 42.5% with a quality of regular feeding, and you grieve 27.5% with an appropriate feeding, it was found that the group maintains a frequency of consumption of food of 2 and 3 times a day but not fractional, these practices associated to the orientation lack and professional advice, also that 92.5% doesn't receive any consultantship type, this at the same time is reflected in its glicemia levels in our study group we have 100% he/she doesn't have the glicemia in the established ranges. Conclusions: Not having an appropriate orientation can take to diabetic complications for under consumption of foods or for a high effort when consuming measures of hydrates of carbon stockings in relation